Sexual Boundary Violations via Digital Media Among Students - Budde, Juergen; Witz, Christina; Böhm, Maika (Frontiers in Psychology, 2022)
As digital media becomes more central to the lives of adolescents, it also becomes increasingly relevant for their sexual communication. Sexting as an important image-based digital medium provides opportunities for self-determined digital communication, but also carries specific risks for boundary violations. Accordingly, sexting is understood either as an everyday, or as risky and deviant behavior among adolescents. In the affectedness of boundary violations gender plays an important role. However, it is still unclear to what extent digital sexual communication restores stereotypical gender roles and restrictive sexuality norms or, alternatively, enables new spaces of possibility. In this sense, current research points to a desideratum regarding adolescents' orientations toward sexting as a practice between spaces of possibility and boundary violations. This paper discusses the possibilities, but also the risks, of intimate digital communication among adolescents. The main question is, how adolescents themselves perceive sexting practices and how they position themselves between both spaces for possibility and for the exchange of unwanted sexual content. For this purpose, orientations towards normalities and gender of students are reconstructed. To answer these questions, twelve single-sex, group discussions were carried out with students aged 16 and 17 at five different secondary schools in northern Germany. A total of 20 boys and 22 girls took part. The group discussions were structured by a narrative generating guideline. The analysis draws its methodology from the Documentary Method, regarding implicit and explicit forms of knowledge and discourse. It results in a typology of three types with different orientations. The study shows, that most of the students consider sexting to be a risky practice; only one type shows normality in the use of sexting. At the same time, some of the young people are interested in experimenting with image-based intimate digital communication. Further, gender differences in use and affectedness are also documented. In this way, orientations towards gender stereotypes ‘favour’ both the attribution of responsibility to girls, and overlook the responsibility of students who perpetrated the boundary violation. The orientations of adolescents should be taken more into account in research as well as in educational programs for the prevention of sexual violence.